2022
DOI: 10.3389/fpls.2021.794906
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics Reveals Regulation of Secondary Metabolites in Mahonia bealei Exposed to Ultraviolet-B Radiation

Abstract: Mahonia bealei (M. bealei) is a traditional Chinese medicine containing a high alkaloid content used to treat various diseases. Generally, only dried root and stem are used as medicines, considering that the alkaloid content in M. bealei leaves is lower than in the stems and roots. Some previous research found that alkaloid and flavonoid contents in the M. bealei leaves may increase when exposed to ultraviolet B (UV-B) radiation. However, the underlying mechanism of action is still unclear. In this study, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…These proteins had a direct correlation with the three features (Figure 8B). The abundance of a second malic enzyme (MAE), also unraveled as relevant by PCA and MOFA (Figure 4 and 6), correlated positively with the abundance of columbamine (Figure 8B), a secondary metabolite increasing under UV-B exposure (Liu et al, 2022).…”
Section: Resultsmentioning
confidence: 89%
“…These proteins had a direct correlation with the three features (Figure 8B). The abundance of a second malic enzyme (MAE), also unraveled as relevant by PCA and MOFA (Figure 4 and 6), correlated positively with the abundance of columbamine (Figure 8B), a secondary metabolite increasing under UV-B exposure (Liu et al, 2022).…”
Section: Resultsmentioning
confidence: 89%
“…RNA extraction and qRT-PCR analysis were performed according to Liu et al [ 46 ]. The primer information used in this study is shown in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, UV-B stress also has the potential to increase the secondary metabolite contents, which can be used by plants for stress resistance . Berberine, jateorhizine, palmatine, and columbamine were increased when Mahonia bealei was exposed to UV-B radiation combined with dark treatment . It has been reported that the concentration of kaempferol increases after UV-B radiation in Arabidopsis thaliana .…”
Section: Introductionmentioning
confidence: 99%
“… 8 Berberine, jateorhizine, palmatine, and columbamine were increased when Mahonia bealei was exposed to UV-B radiation combined with dark treatment. 9 It has been reported that the concentration of kaempferol increases after UV-B radiation in Arabidopsis thaliana . ( 10 ) UV-B followed by dark treatment also increased the contents of coumarins in C. terniflora according to a previous study, 11 and the ATP content increased to provide energy for secondary metabolism.…”
Section: Introductionmentioning
confidence: 99%